Effect of Silane Solvent on Microtensile Bond Strength of Hy-drogen Peroxide-Treated Fiber Post and Composite Core - Sh. Kasraei; Sh. Ebadi; M. Atai; Z. Khamverdi; S. Khajeh (Tehran University of Medical Sciences, 2008)
Objective: The aim of this in vitrostudy was to evaluate the effect of the type of solvent in silane solution on microtensile bond strength of fiber posts to composite resin cores af-ter application of 24% hydrogen peroxide. Materials and Methods: Eighteen white fiber posts, immersed in 24% hydrogen peroxide were divided into three groups (n=6). In the group A post surfaces were silanized with an ethanol based solution, in group B with an acetone based solution, in the group C with and un-diluted methacryloxytrimethoxysilane (as the control group). The cores were built up using flowable composite. Microtensile bond strength test and evaluations using stereomi-croscope were performed on the samples and the data were analyzed using one-way ANOVA and Tukey HSD tests. Results: A significant difference was observed between the amounts of microtensile bond strength of fiber poststo composite cores in the groups A and B, and the ones in group C (P<0.05). There was no such difference between groups A and B (P>0.05). Conclusion: The type of solvent in silane solution has no effect on microtensile bond strength between fiber post andcomposite resin core after application of 24% Hydrogen Peroxide.